2015
DOI: 10.1002/gj.2640
|View full text |Cite
|
Sign up to set email alerts
|

Subduction initiation of Indochina and South China blocks: insight from the forearc ophiolitic peridotites of the Song Ma Suture Zone in Vietnam

Abstract: The Song Ma region, which is located in the northwestern Vietnam represents the zone of amalgamation between Indochina and South China blocks. Numerous scattered ultramafic rocks occur in this region in association with Early to Middle Palaeozoic greenschists and paragneisses, and all these rocks were subjected to hydrous metamorphism and deformation. Here, we present new field data, mineral chemistry and geochemistry from a suite of hydrated peridotites within the Song Ma region and discuss the tectonic signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 127 publications
(318 reference statements)
0
10
0
Order By: Relevance
“…The northern Song Chay mélange and southern Song Ma suture zone mark the opening and closure of the paleo-Tethys Ocean (Metcalfe, 1996(Metcalfe, , 2013Trung et al, 2006;Vượ;ng et al, 2013;Zhang et al, 2013Zhang et al, , 2014. The Cenozoic left-lateral movement along the Ailaoshan belt offset South China from the Indochina Block (Faure et al, 2014(Faure et al, , 2016a(Faure et al, , 2016bNgo et al, 2016;Zhang et al, 2013).…”
Section: Adjacent Tectonic Units Of Nanpanjiang Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…The northern Song Chay mélange and southern Song Ma suture zone mark the opening and closure of the paleo-Tethys Ocean (Metcalfe, 1996(Metcalfe, , 2013Trung et al, 2006;Vượ;ng et al, 2013;Zhang et al, 2013Zhang et al, , 2014. The Cenozoic left-lateral movement along the Ailaoshan belt offset South China from the Indochina Block (Faure et al, 2014(Faure et al, , 2016a(Faure et al, , 2016bNgo et al, 2016;Zhang et al, 2013).…”
Section: Adjacent Tectonic Units Of Nanpanjiang Basinmentioning
confidence: 99%
“…The major structural features in South China include a foreland basin and an intra-Late Triassic angular unconformity, NW-, or WNW striking fold-thrust belt, and greenschist facies metamorphism in the hinterland (e.g., Faure et al, 2014;Hu et al, 2015;H. C. Liu, Wang, et al, 2015;Ngo et al, 2016;Qiu et al, 2017;Shu et al, 2009;Wang et al, 2018;Yang et al, 2018;R. Q. Zhang, Zhou, et al, 2009; Y. Q.…”
Section: Phanerozoic Tectonic Events In South Chinamentioning
confidence: 99%
“…Previous studies on regional tectonics have shown that the Indochina was undergone by two mainly tectonics, which is Indochina-South China subduction/collision during the Permian-Triassic (Ngo et al, 2016;Roger et al, 2012) and India-Asia collision commenced during the Cenozoic (Aitchison et al, 2007;Bui et al, 2018;Zhao et al, 2020;Hoang et al, 2016Hoang et al, , 2017. The Cenozoic igneous activities in southeast China and Indochina occurred in two episodes at 42-24 Ma and 16-0 Ma (Fig.…”
Section: Implications For Crustal Evolutionmentioning
confidence: 99%
“…(3) Late Carboniferous-Early Permian (ca. 310-280 Ma): I-type granite, granodiorite, and diorite were emplaced in the southern Truong Son area (Ngo et al, 2014(Ngo et al, , 2016Pham et al, 2017;Qian et al, 2020) (Pham N.C. et al, 2020;Wang et al, 2016;Tran et al, 2014). A small number of alkaline intrusions in the northern Truong Son terrane have Middle-Late Triassic ages and were formed during the closure of the Song Ma ocean and collision of the South China and Indochina block.…”
Section: Geological Settingmentioning
confidence: 99%
“…prolongation of the Jingshajiang-Ailaoshan belt (Hieu, Li, et al, 2016;Nakano et al, 2008Nakano et al, , 2010Ngo et al, 2015;Shi et al, 2015;Trung et al, 2006;Vượng et al, 2013;Y. Wang, Qian, et al, 2018;Wen et al, 2015;R.…”
mentioning
confidence: 99%